2021
DOI: 10.1007/s00296-021-04886-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported effectiveness and safety of Pamidronate in NSAIDs-refractory chronic recurrent multifocal osteomyelitis in children

Abstract: To evaluate patient-reported effectiveness, safety and social influence of Pamidronate in the therapy of NSAIDs-refractory Chronic Recurrent Multifocal Osteomyelitis in children. Authors reviewed self-created questionnaires, which asked patients for symptoms alleviation, adverse drug reactions frequency and degree of severity and daily activities self-reliance. Only surveys with complete answers, which were returned to authors by an e-mail from juvenile patients treated for NSAIDs-refractory Chronic Recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…The safety of Pamidronate treatment was also supported by Jjuszczak et al, who found that 39 out of 42 (93%) patients agreed Pamidronate is effective for NSAIDsrefractory chronic recurrent multifocal osteomyelitis in children, without reported prominent side effects. 37 Demographic characteristics from each study significantly differed from others. The age in some studies varied greatly, while those in others varied considerably.…”
Section: Discussionmentioning
confidence: 88%
“…The safety of Pamidronate treatment was also supported by Jjuszczak et al, who found that 39 out of 42 (93%) patients agreed Pamidronate is effective for NSAIDsrefractory chronic recurrent multifocal osteomyelitis in children, without reported prominent side effects. 37 Demographic characteristics from each study significantly differed from others. The age in some studies varied greatly, while those in others varied considerably.…”
Section: Discussionmentioning
confidence: 88%